(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The practice of Triple Talaq, a form of unilateral divorce in Islamic law, has been a subject of intense scrutiny, debate, and legal reforms in recent years. This article comprehensive exploration & delves into the multi-faceted dimensions of this practice, from its historical foundations to its contemporary implications on gender equality, women’s rights, religious freedom, and social justice. The journey of this article begins with an in-depth examination of the historical roots of Triple Talaq, tracing its evolution through Islamic jurisprudence. It highlights the variations and interpretations of this practice across different Islamic schools of thought, shedding light on the complex debates that have arisen within the Muslim world. The heart of the discourse lies in the controversies surrounding Triple Talaq. This article explores how the practice perpetuates gender disparities and leaves women vulnerable to economic, emotional, and legal hardships. It dissects the absence of legal recourse for women affected by Triple Talaq, laying bare the challenges they face in seeking justice within religious and secular legal systems. The narrative then shifts to the legal developments and reforms that have reshaped the landscape of Triple Talaq. The landmark Indian case of Shayara Bano v. Union of India and the subsequent enactment of the "Muslim Women (Protection of Rights on Marriage) Act, 2019" exemplify the strides taken to address the injustices associated with Triple Talaq. These legal reforms offer critical insights into the delicate balance between religious traditions and contemporary ideals of justice and equality. A global perspective illuminates how different nations, both Muslim-majority countries and those with Muslim minority communities, have engaged with Triple Talaq. It underscores the diverse approaches and common themes that have emerged in navigating the complexities of religious freedom, cultural diversity, and gender equality. Throughout this article journey, several points have emerged. The intersection of tradition and modernity, the importance of inclusivity, the delicate balance between rights and responsibilities, the role of constructive dialogue, and the significance of legal frameworks in safeguarding individual rights are among the valuable takeaways. This article is not merely an exploration of a single practice but a reflection of broader societal debates. It prompts us to consider how tradition and modernity can coexist, how rights and responsibilities intersect, and how dialogue and legal frameworks can shape our pursuit of a more just and equitable world. The quest for understanding Triple Talaq transcends geographical boundaries, resonating as a global endeavor for gender justice, religious freedom, and social harmony